Microscale Pore Throat Differentiation and Its Influence on the Distribution of Movable Fluid in Tight Sandstone Reservoirs. (7th January 2021) - Dong, Fengjuan; Lu, Xuefei; Cao, Yuan; Rao, Xinjiu; Sun, Zeyong
Abstract : Tight sandstone reservoirs have small pore throat sizes and complex pore structures. Taking the Chang 6 tight sandstone reservoir in the Huaqing area of the Ordos Basin as an example, based on casting thin sections, nuclear magnetic resonance experiments, and modal analysis of pore size distribution characteristics, the Chang 6 tight sandstone reservoir in the study area can be divided into two types: wide bimodal mode reservoirs and asymmetric bimodal mode reservoirs. Based on the information entropy theory, the concept of "the entropy of microscale pore throats" is proposed to characterize the microscale pore throat differentiation of different reservoirs, and its influence on the distribution of movable fluid is discussed. There were significant differences in the entropy of the pore throat radius at different scales, which were mainly shown as follows: the entropy of the pore throat radius of 0.01 0.1 μ m, >0.1 μ m, and <0.01 μ m decreased successively; that is, the complexity of the pore throat structure decreased successively. The correlation between the number of movable fluid occurrences on different scales of pore throats and the entropy of microscale pore throats in different reservoirs is also different, which is mainly shown as follows: in the intervals of >0.1 μ m and 0.01 0.1 μ m, the positive correlation between the occurrence quantity of movable fluid in the wide bimodal mode reservoir is better than that in the asymmetric bimodal mode reservoir. However, there was a negative correlation between the entropy of the pore throat radius and the number of fluid occurrences in the two types of reservoirs in the pore throat radius of <0.01 μ m. Therefore, pore throats of >0.1 μ m and 0.01 0.1 μ m play a controlling role in studying the complexity of the microscopic pore throat structure and the distribution of movable fluid in the Chang 6 tight sandstone reservoir. The above results deepen the understanding of the pore throat structure of tight sandstone reservoirs and present guiding significance for classification evaluation, quantitative characterization, and efficient development of tight sandstone reservoirs.